Cutting force impact to tool life of CT5015 in high speed machining by applying negative rake angles - Adesta, Erry Yulian Triblas; Riza, Muhammad; Ali, Mohammad Yeakub (Trans Tech Publications Ltd., Switzerland, 2012)
Cermets become increasingly popular cutting insert in recent years. They are generally good when accuracy and finish are criteria for the operation. Several improvements have been made to increase their performance in machining process such as higher resistance to thermal deformation and lower conductivity than carbide tools that wear rapidly. This study is to investigate cutting force and tool wear under different rake angles in high speed machining process. Experiments were carried out by using cermet insert (CT5015). Different rake angles have been applied in the experiments which are 0o, -3o. -6o, -9o and -12o respectively with cutting speed 1000 m/minute and feed rate 800 mm/minute. For every single pass of cutting, cutting force, wear rate and cutting temperature were measured respectively by surface roughness tester, dynamometer, Scanning Electron Microscope (SEM) and infrared thermometer. The experimental results showed that the more negative angles the higher cutting force produced. Simultaneously, cutting temperature increases following the incremental of cutting force. It caused wear occurred faster and lead to reduce the life of cermet inserts.